2019
DOI: 10.1111/jwas.12604
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory costs on U.S. salmonid farms

Abstract: The economic effects of the implementation of regulations on aquaculture farms in the United States, while of concern, are not well understood. A national survey was conducted of salmonid (trout and salmon) farms in 17 states of the United States to measure on‐farm regulatory costs and to identify which regulations were the most costly to this industry segment. The response rate was 63%, with a coverage rate of 94.5% of the U.S. production of salmonids. The regulatory system resulted in increased national on‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 24 publications
(33 reference statements)
5
61
2
Order By: Relevance
“…Nevertheless, increasing numbers of studies are pointing to an aquaculture business environment in the U.S. that may have become excessively convoluted, redundant, and inefficient in terms of achieving the societal goals expressed in the original legislation underlying the various laws that govern the U.S. More specific to aquaculture, previous studies on on-farm economic effects of the regulatory system in the U.S. have shown the regulatory compliance burden to be of an order of magnitude that warrants efforts to seek more cost-efficient ways to provide the same level of rigor and oversight. Given that shellfish is a large segment of U.S. aquaculture, it is not surprising that the total values of the regulatory cost burden on farms measured in this study were greater than those in previous studies of the salmonid and baitfish/sportfish sectors in the U.S (Engle et al, 2019;van Senten & Engle, 2017). The proportion of the mean cost of licenses and permits for Pacific coast shellfish (4%), however, was similar to the percentages calculated for U.S. baitfish and sportfish (1%) and U.S. salmonid (2%) aquaculture (Engle et al, 2019;van Senten & Engle, 2017).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, increasing numbers of studies are pointing to an aquaculture business environment in the U.S. that may have become excessively convoluted, redundant, and inefficient in terms of achieving the societal goals expressed in the original legislation underlying the various laws that govern the U.S. More specific to aquaculture, previous studies on on-farm economic effects of the regulatory system in the U.S. have shown the regulatory compliance burden to be of an order of magnitude that warrants efforts to seek more cost-efficient ways to provide the same level of rigor and oversight. Given that shellfish is a large segment of U.S. aquaculture, it is not surprising that the total values of the regulatory cost burden on farms measured in this study were greater than those in previous studies of the salmonid and baitfish/sportfish sectors in the U.S (Engle et al, 2019;van Senten & Engle, 2017). The proportion of the mean cost of licenses and permits for Pacific coast shellfish (4%), however, was similar to the percentages calculated for U.S. baitfish and sportfish (1%) and U.S. salmonid (2%) aquaculture (Engle et al, 2019;van Senten & Engle, 2017).…”
Section: Discussioncontrasting
confidence: 62%
“…For example, van Senten & Engle, 2017 found annual average on-farm regulatory compliance costs on U.S. baitfish/sportfish farms to be $148,554 per farm, or $7,383 per hectare. Engle et al (2019), in a similar study of U.S. salmonid (trout and salmon) farms, found the annual average on-farm regulatory compliance costs to be $165,187 per farm and $2.71/kg of salmonid production. Both studies showed disproportionately greater annual regulatory costs on smaller-scale as compared to larger-scale farms.…”
Section: Introductionmentioning
confidence: 95%
“…These programs have been at various levels, often in vocational agricultural programs in high schools or two‐year college programs as well as four‐year and graduate university programs (European Commission, 2009; Curtotti, Hormis, & McGill, 2012; Jensen et al, 2015, 2016; Pita et al, 2015; Evans, 2019). Nevertheless, in a series of recent extensive surveys of aquaculture producers in the United States, a shortage of labor was cited as one of the top five problems confronting aquaculture producers (Engle, van Senten, & Fornshell, 2019; van Senten & Engle, 2017; van Senten, Engle, Hudson, & Conte, 2020; van Senten, Engle, & Smith, 2020). In Australia, an aging workforce in aquaculture and issues of recruitment and retention of an adequate workforce for aquaculture were described as growing problems (Curtotti et al, 2012).…”
mentioning
confidence: 99%
“…Nevertheless, in a series of recent extensive surveys of aquaculture producers in the United States, a shortage of labor was cited as one of the top five problems confronting aquaculture producers (Engle, van Senten, & Fornshell, 2019; van Senten & Engle, 2017; van Senten, Engle, Hudson, & Conte, 2020; van Senten, Engle, & Smith, 2020). In Australia, an aging workforce in aquaculture and issues of recruitment and retention of an adequate workforce for aquaculture were described as growing problems (Curtotti et al, 2012).…”
mentioning
confidence: 99%
“…In addition to the need for more analyses of farm-level data that measure sets of environmental, economic, and social sustainability metrics, there are other aspects of global sustainability that require additional research. The emerging research on the relative governance related to sustainability issues around the world suggests that the disparity in stringency of regulations may be driving aquaculture production away from developed countries that have stringent sets of regulations and enforcement to the developing world with less stringent regulatory systems (Abate, Nielsen, & Tveterås, 2016;Engle and Stone, 2013;Engle, van Senten, & Fornshell, 2019;van Senten & Engle, 2017; van Senten, Dey, & Engle, 2018). The effect of the widely disparate levels of regulatory stringency can be seen with regard to the large volumes of low-priced pangasius sold from Vietnam.…”
mentioning
confidence: 99%